Manipulating RKIP reverses the metastatic potential of breast cancer cells - Lai, Trang Huyen; Ahmed, Mahmoud; Hwang, Jin Seok; Bahar, Md Entaz; Pham, Trang Minh; Yang, Jinsung; Kim, Wanil; Maulidi, Rizi Firman; Lee, Dong-Kun; Kim, Dong-Hee; Kim, Hyun Joon; Kim, Deok Ryong (Frontiers in Oncology, 2023)
Breast cancer is a common tumor type among women, with a high fatality due to metastasis. Metastasis suppressors encode proteins that inhibit the metastatic cascade independent of the primary tumor growth. Raf kinase inhibitory protein (RKIP) is one of the promising metastasis suppressor candidates. RKIP is reduced or lost in aggressive variants of different types of cancer. A few pre-clinical or clinical studies have capitalized on this protein as a possible therapeutic target. In this article, we employed two breast cancer cells to highlight the role of RKIP as an antimetastatic gene. One is the low metastatic MCF-7 with high RKIP expression, and the other is MDA-MB-231 highly metastatic cell with low RKIP expression. We used high-throughput data to explore how RKIP is lost in human tissues and its effect on cell mobility. Based on our previous work recapitulating the links between RKIP and SNAI, we experimentally manipulated RKIP in the cell models through its novel upstream NME1 and investigated the subsequent genotypic and phenotypic changes. We also demonstrated that RKIP explained the uneven migration abilities of the two cell types. Furthermore, we showed that chemically manipulating RKIP expression inhibited the migration of the highly metastatic cells. Finally, we identified the regulatory circuit that might carry the effect of an existing drug, Epirubicin, on activating gene transcription. In conclusion, in the study, we propose and test a potential strategy to reverse the metastatic capability of breast cancer cells by chemically manipulating RKIP expression. Furthermore, we highlight a potential functional link between RKIP and the estrogen receptor.